2020
DOI: 10.1016/j.micromeso.2019.109783
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of nanosized MgFe2O4 nanoparticles in phenylene-bridged KIT-6-type ordered mesoporous organosilica (PMO)

Abstract: The unique combination of two functional materials, namely the earth-abundant spinel magnesioferrite (MgFe 2 O 4) and mesoporous phenylene-bridged KIT-6-type organosilica, was developed. The mesoporous organosilica acts as host matrix for the nanosized MgFe 2 O 4 particles which leads to better dispersibility and increased stability towards acids. Additionally, the mesoporous host is a very good material to generate a toolbox towards applicable materials due to flexible functionalization. Nanosized, monodisper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 89 publications
(111 reference statements)
3
4
0
Order By: Relevance
“…2 f). Accordingly, these patterns agreeing with the ( Ia-3d ) symmetry and indicate the presence of well-defined pores before and after surface modification of M-PMO [ 73 , 74 ]. The observed decrease in the intensity of the reflections, without change in their position and pattern suggests the success of functionalization as well as the retention of the meso-porosity characteristic of AGu@PEG 1500 -PMO during surface modification.…”
Section: Resultssupporting
confidence: 75%
“…2 f). Accordingly, these patterns agreeing with the ( Ia-3d ) symmetry and indicate the presence of well-defined pores before and after surface modification of M-PMO [ 73 , 74 ]. The observed decrease in the intensity of the reflections, without change in their position and pattern suggests the success of functionalization as well as the retention of the meso-porosity characteristic of AGu@PEG 1500 -PMO during surface modification.…”
Section: Resultssupporting
confidence: 75%
“…The solid is recovered and the surfactant template is removed, mostly by extraction, but due to the high thermal stability of Si-C bonds and selected organic bridges, in specific cases, using carefully established protocols, also calcination may be possible to at least partially remove the surfactant, while retaining the organic groups in the framework. 122,123 PMOs have not been as extensively studied for use in drug delivery as their pure silica counterparts (possibly modified with pending organic groups). This has been attributed to the more difficult synthesis of uniform and discrete PMO nanoparticles (NPs) with adjustable properties on the one hand, and lack of information on bio-safety of PMO nanoparticles on the other.…”
Section: Historical Background Of the Synthesis Of Ordered Mesoporous...mentioning
confidence: 99%
“…The solid is recovered and the surfactant template is removed, mostly by extraction, but due to the high thermal stability of Si–C bonds and selected organic bridges, in specific cases, using carefully established protocols, also calcination may be possible to at least partially remove the surfactant, while retaining the organic groups in the framework. 122,123…”
Section: Introductionmentioning
confidence: 99%
“…KIT‐6 build‐up from the three‐dimensional bicontinuous cubic structure is among mesoporous silica materials which have been used as catalyst, gas adsorbent and separator, supercapacitor, electrode, and so on 28–30 . KIT‐6 has a high surface area per volume ratio, high hydrothermal stability, large and tunable cylindrical pores with high interconnectivity and thick walls 31 . KIT‐6 has advantages over one‐dimensional and two‐dimensional mesoporous structures due to its ordered three‐dimensional pore structure with two intertwined systems of mesoporous channels providing more active sites for functionalization, more resistance to pore blocking, and more permeability without sacrificing the selectivity 32 .…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] KIT-6 has a high surface area per volume ratio, high hydrothermal stability, large and tunable cylindrical pores with high interconnectivity and thick walls. 31 KIT-6 has advantages over one-dimensional and two-dimensional mesoporous structures due to its ordered three-dimensional pore structure with two intertwined systems of mesoporous channels providing more active sites for functionalization, more resistance to pore blocking, and more permeability without sacrificing the selectivity. 32 It has been shown that the addition of KIT-6 to the polymeric matrix enables the fabrication of intimate composites due to the penetration of polymer chains into the relatively large pores of the mesoporous.…”
mentioning
confidence: 99%